CD4 Cell Count: Declining Value for Antiretroviral Therapy Eligibility - Ying, Roger; Granich, Reuben M; Gupta, Somya; Williams, Brian G (Clinical infectious diseases, 2016)
Antiretroviral therapy (ART) policy for people living with human immunodeficiency virus (HIV) has historically been based on clinical indications, such as opportunistic infections and CD4 cell counts. Studies suggest that CD4 counts early in HIV infection do not predict relevant public health outcomes such as disease progression, mortality, and HIV transmission in people living with HIV. CD4 counts also vary widely within individuals and among populations, leading to imprecise measurements and arbitrary ART initiation. To capture the clinical and preventive benefits of treatment, the global HIV response now focuses on increasing HIV diagnosis and ART coverage. CD4 counts for ART initiation were necessary when medications were expensive and had severe side effects, and when the impact of early ART initiation was unclear. However, current evidence suggests that although CD4 counts may still play a role in guiding clinical care to start prophylaxis for opportunistic infections, CD4 counts should cease to be required for ART initiation.